2017
DOI: 10.1136/bmjquality.u223876.w5716
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Patient Safety Event Reporting in an Emergency Medicine Residency

Abstract: Patient safety event reporting is an important component for fostering a culture of safety. Our tertiary care hospital utilizes a computerized patient safety event reporting system that has been historically underutilized by residents and faculty, despite encouragement of its use. The objective of this quality project was to increase patient safety event reporting within our Emergency Medicine residency program. Knowledge of event reporting was evaluated with a survey. Eighteen residents and five faculty parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(11 reference statements)
0
7
0
Order By: Relevance
“… 7 There is also knowledge gaps on what is considered as reportable patient safety event. 21 Discussing errors with seniors or supervisors had a positive attitude shown by higher mean score in our study. Similar results by various other researches showed that disclosing mistakes may help physicians to learn.…”
Section: Discussionmentioning
confidence: 43%
“… 7 There is also knowledge gaps on what is considered as reportable patient safety event. 21 Discussing errors with seniors or supervisors had a positive attitude shown by higher mean score in our study. Similar results by various other researches showed that disclosing mistakes may help physicians to learn.…”
Section: Discussionmentioning
confidence: 43%
“…64 Smith et al 63 described how pediatric residents developed a curriculum and led a monthly conference during which they reviewed adverse event reports, identified system vulnerabilities, and designed solutions to address those vulnerabilities. As part of educational programming, morbidity and mortality conferences were used to increase trainee awareness about adverse events and the importance of reporting 31,34,53,57,63,74,[76][77][78][79] ; however, although there were calls for increased trainee participation in RCA), 19 only Murphy and colleagues 60 described an intervention using a mock RCA to increase trainee adverse event reporting, and only the study by Dunbar and colleagues 52 reported increased resident physician involvement in RCA as a result of their intervention.…”
Section: Figurementioning
confidence: 99%
“…59 With regard to reinforcing factors, 22 of those 42 articles (52%)## addressed how programs used feedback or incentives to promote patient safety event reporting. Steen and colleagues 19 developed an educational session on event reporting and followed up by providing feedback every 2 months on events reported and actions taken. Finally, 18 of the 42 articles (43%)*** discussed the use of behavioral modeling or training to address attitudes and beliefs; for example, Boike and colleagues 21 used 1-hour training conferences to educate residents on the types of events that qualify for adverse event reporting.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that in US states where reporting of adverse events is mandatory, reports submitted by individuals (contrasted with automated reporting) have improved safety and reduced harm at the institutional level after root cause analysis. 2 However, this positive outcome was found in the context of (1) voluntary reporting and (2) conducting a root cause analysis. We wonder whether voluntary reporting is comparable to incentivized reporting and whether root cause analyses were conducted following the receipt of the incentivized safety reports.…”
mentioning
confidence: 99%